Viscoelastic shear damping mechanism for vibration reduction on a helicopter anti-torque beam - Bottasso, L.M.; Ghrinighelli, G.; Perazzolo, A.; Fosco, E.; Ricciardi, M.; Goh See, S.; Vigoni, E.; Cordisco, P.; Terraneo, M.; Vertel, J. (My University, 2017)
We describe the design and test of improved versions of the anti-torque beam (ATB) of the AW139 twin-engine helicopter, featuring multi-layered viscoelastic damping treatment. Viscoelastic material sheets have been embedded in the component to damp vibrations over a wide frequency spectrum. The new configuration is called hybrid anti-torque beam (HATB). Two approaches have been pursued; in the first, a completely new multi-layer laminated beam was built, replacing the original monolithic structure with a sandwich of metal sheets interposed with viscoelastic material. Different sub-cases were explored and ground-tested. The second configuration, which is easier to qualify for flight test, was based on a standard production beam. The part was coated on both sides with a proprietary high-damping treatment, suitably constrained in order to activate a shear strain mode. The adoption of high-damping material in a structural component such as the ATB facilitates the dissipation of mechanical energy in transit through the part, before it is converted into acoustic energy. The location of the ATB is strategic in this respect because it represents a privileged transfer path for vibrations generated by the main rotor, transmission gearbox, engines, pumps, cooling fans and other utilities. A test campaign offered some experimental insight on those design factors which mostly affect the damping, aimed at achieving an optimal trade-off between structural stiffness, weight and loss factor. The preliminary flight and ground tests of the HATB have shown that it can be effective in attenuating the noise transmitted to the helicopter cabin. These results will enable further development and testing of multi-layer HATB designs.